PERFORMANCE OF HEALTH SERVICES IN HANDLING COVID-19 IN CIAMIS DISTRICT (DESCRIPTION STUDY OF SERVICE PERFORMANCE IN HEALTH HANDLING) - Nizar Adhari; Sirodjul Munir (Faculty of Social And Political Science Universitas Galuh, 2022)
This research was motivated by the fact that the Health Department's performance was not yet optimal in handling health which led to a continuous increase in Covid-19 cases in Ciamis Regency. The low responsiveness of the Health Service in carrying out Covid-19 surveillance in the community, the function of the support system for positive Covid-19 patients in recovery has not yet been implemented and the monitoring, control and regulation of Covid-19 handling activities in the Ciamis district has not been effective. The formulation of the research problem is: 1) How is the performance of the Health Office in handling Covid-19 in Ciamis Regency?. 2). What are the obstacles faced in handling Covid-19 in Ciamis Regency?, 3) How are the efforts made to improve the performance of the Ciamis District Health Office in handling Covid-19 in Ciamis District?. The method used in this research is by using qualitative research methods. The number of informants in this study were 7 people. The data collection techniques there are two types of data, namely primary data and secondary data including interviews, observations and documentation. Data processing/analysis techniques in this research are data reduction, data display, conclusion drawing and verification. Based on the results of the study that: 1) The performance of the Health Office in Ciamis Regency in general has been implemented but has not been optimal. 2) The obstacles faced to improve the performance of the Health Office in handling Covid-19 in Ciamis Regency are the lack of cooperation and coordination, the lack of readiness of employees to go down to remote areas that require socialization of the spread of Covid-19 and lack of Human Resources. 3) Efforts are being made to overcome obstacles to improve the performance of the Health Office in handling Covid-19 in Ciamis Regency, namely the addition of Human Resources, socializing about the prevention and handling of Covid-19, establishing cooperation and coordinating with various parties to accelerate and monitoring in the Ciamis Regency community. lack of readiness of employees to go down to remote areas that require socialization of the spread of Covid-19 and lack of human resources. 3) Efforts are being made to overcome obstacles to improve the performance of the Health Office in handling Covid-19 in Ciamis Regency, namely the addition of Human Resources, socializing about the prevention and handling of Covid-19, establishing cooperation and coordinating with various parties to accelerate and monitoring in the Ciamis Regency community. lack of readiness of employees to go down to remote areas that require socialization of the spread of Covid-19 and lack of human resources. 3) Efforts are being made to overcome obstacles to improve the performance of the Health Office in handling Covid-19 in Ciamis Regency, namely the addition of Human Resources, socializing about the prevention and handling of Covid-19, establishing cooperation and coordinating with various parties to accelerate and monitoring in the Ciamis Regency community.